ELASTIC-PLASTIC STRESS-DISTRIBUTION IN THE ROTATING ANNULAR DISK WITH VARIABLE THICKNESS - GUVEN, U (SPRINGER VERLAG, 1991)
The plane state of stress in a rotating annular disk with variable thickness is studied. The analysis is based on Tresca's yield condition, its associated flow rule and linear strain hardening.
Keywords: Mechanics